2017
DOI: 10.1016/j.nme.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the impact of an RF sheath on the Scrape-Off Layer in 2D and 3D turbulence simulations

Abstract: International audienceMotivated by Radio Frequency (RF) heating studies, the response of the plasma of tokamaks to the presence of a locally polarized limiter is studied. In a first part, we use the TOKAM3X 3D global edge turbulence code to analyse the impact of such biasing in a realistic geometry. Key features of experimental observations are qualitatively recovered, especially the extension of a potential and density perturbation on long, but finite, distances along connected field lines. The perturbation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Experiments in AUG showed that the shear flow generated by ICRF-sheath rectification in the SOL can poloidal stretch or even split the filaments [84]. Simulation with the fluid turbulence code TOKAM has explored the influence of a localized DC bias of the wall on SOL turbulence [152]. The conclusion is that the density inside the convective cells is depleted, the shear flow tears the filaments apart and the fluctuation amplitude decreases locally, which is consistent with the experimental findings.…”
Section: Icrf-edge Turbulence Interactionsupporting
confidence: 72%
“…Experiments in AUG showed that the shear flow generated by ICRF-sheath rectification in the SOL can poloidal stretch or even split the filaments [84]. Simulation with the fluid turbulence code TOKAM has explored the influence of a localized DC bias of the wall on SOL turbulence [152]. The conclusion is that the density inside the convective cells is depleted, the shear flow tears the filaments apart and the fluctuation amplitude decreases locally, which is consistent with the experimental findings.…”
Section: Icrf-edge Turbulence Interactionsupporting
confidence: 72%
“…It also naturally explains the observed origin of the parallel RF power flow from the SOL in front of the antenna rather than from the antenna surface itself 26 . It does not contradict any of the existing proposed explanations: Wavefilament bound states could act in synergy with the "opening" of the boundary plasma to FW propagation 27 , and with sheath rectification and the subsequent parallel spread of DC bias via DC current transport [28][29][30] . In future work, we will use Finite Element calculations to ascertain to what extent the claims in this paper depend on the unrealistic assumptions made in the Mie solution, such as non-circular filament cross sections, steep but continuous density gradients at the filament interface, and nonconstant background density.…”
mentioning
confidence: 57%
“…This could, in some cases, be the normal SOL turbulence that is always present, but more likely, when strong RF-driven convection is present, the turbulence may be caused by flow instabilities such as the Kelvin-Helmholtz instability. Some theoretical work on turbulent cross-field conductivity in this type of situation is presented in Tamain et al (2017) where a fluid turbulence code is employed.…”
Section: Global DC Circuitsmentioning
confidence: 99%